Interfacial reaction and side effect of MgB2 superconducting material through low-rotation mechanical milling. Issue 5 (1st March 2022) - Maeda, Minoru; Heo, Yoon-Uk; Choi, Jun Hyuk; Patel, Dipak; Kim, Su-Hun; Hahn, Seungyong; Kim, Jung Ho; Choi, Seyong
Abstract: Powder processing by ball milling is an effective approach for materials engineering. Although various methods for material processing are available, only high-energy shaker/vibratory or planetary mills have been intensively utilized to develop mechanical milling or alloying routes for structural control of MgB2 superconducting materials. Herein, we have attempted structural modification by using a low-rotation shaker, which is categorized as a low-energy and economical mill in terms of industrial applications. The operation speed was kept constant at 40 rpm, which is much lower than typical conditions employed for planetary mills. Instead of adjusting the low rotational speed, the other processing parameters were controlled to enhance the energy transfer from the balls to powders. The applied milling conditions were ultimately found to cause severe plastic deformation of the raw powders. The shape and size changed drastically, depending on the processing time. The morphological variation of the processed powders as precursors for the MgB2 materials influenced the void structure and the composition including amorphous phases. By considering these results, we also elucidated the mechanism underlying the structural changes upon ball milling and their effects on the transport critical current performance. The present approach for powder processing offers potential as an effective milling route for structural modification of superconducting materials.